2012
DOI: 10.1002/cmmi.1477
|View full text |Cite
|
Sign up to set email alerts
|

Processing of superparamagnetic iron contrast agent ferucarbotran in transplanted pancreatic islets

Abstract: Labeling of pancreatic islets with superparamagnetic iron oxide (SPIO) nanoparticles enables their post-transplant monitoring by magnetic resonance imaging (MRI). Although the nanoparticles are incorporated into islet cells in culture, little is known about their fate in vivo. We studied the morphology of labeled islets after transplantation, aiming to identify the MRI contrast particles and their relationship to transplantation outcomes. Rat islets labeled with the ferucarbotran were transplanted into the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
3
16
0
Order By: Relevance
“…Herein, in vivo histologic analysis showed iron labeling mainly around functional islets. This observation is in accordance with Zacharovova et al who described translocation of the ferucarbotran particles from the endocrine cells to the host-derived macrophages surrounding the vital islets in a model of intraportal and kidney subcapsular transplantation in rat (27). Although iron labeling was no longer associated with endocrine cells, iron could be detected near the islet as long as the islet was still functioning.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Herein, in vivo histologic analysis showed iron labeling mainly around functional islets. This observation is in accordance with Zacharovova et al who described translocation of the ferucarbotran particles from the endocrine cells to the host-derived macrophages surrounding the vital islets in a model of intraportal and kidney subcapsular transplantation in rat (27). Although iron labeling was no longer associated with endocrine cells, iron could be detected near the islet as long as the islet was still functioning.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, when rejection occurred, iron was found in recently rejected islets, explaining why 50% to 60% of the signal temporarily persisted. In a similar model, Zacharovova et al detected iron in macrophages near recently rejected islets on day 9 but only weakly after day 14 (27), suggesting rapid clearance. However, with models of slower rejection, some authors have reported persistence of iron labeling around rejected islets potentially giving false-positive results in further clinical application.…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, several studies were conducted to perform in vivo imaging of transplanted islets, which were labeled before transplantation with, for example, iron oxide-, manganite-or gadolinium-based nanoparticles CAs (8,(10)(11)(12)(13)(14)(15)(16)(17). However, only few attempts were made to noninvasively visualize and monitor endogenous native islets in the pancreas in vivo by means of MRI.…”
Section: Comparison With Other Methodsmentioning
confidence: 99%
“…In both cases, a high concentration of glucose catalyzed the targeted labeling process, which for Mn 2+ resulted in the influx of the contrast agent into the β-cells, and for the gadolinium-based sensor in a release of Zn 2+ ions by glucose-induced insulin secretion. MRI is also capable of visualizing single pancreatic islet grafts after ex vivo labeling with ironoxide or manganite-based nanoparticles (NPs) and subsequent implantation into the liver or a subcutaneous chamber (8,(10)(11)(12)(13)(14)(15)(16)(17). Individual native islets have been recently observed in vivo after systemic administration of Mn 2+ in the externalized and immobilized pancreas (18).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown a positive correlation between islet engraftment and function and islet image, 39 , 70 but there are some obstacles to promoting this methodology at the clinical level. Recently Zacharovova and colleagues confirmed that SPIOs in the transplanted islets were taken into phagocytic cells including macrophages, and that the hypointensive spots on T2WI MRI might not reflect engrafted islets alone 71 . This means that the number of obtained signals might not reflect the number of engrafted islets, which could lead physicians to misinterpret the engraftment of islets (i.e., by leading to false-positive results).…”
Section: Mrimentioning
confidence: 99%